Improving Mathematics Learning Outcomes Using the Problem Based Learning Model at SMP Negeri 7 Binamu - Husriani Husain; Syaharuddin; Mutmainna Ekawati; Yasriuddin (Jurnal Syntax Admiration, 2021)
Mathematics learning is still centered on the conventional model where the teacher has high authority while the student is the object of learning. This study aims to apply the Problem-Based Learning (PBL) learning method to increase student mathematics learning activities and outcomes. The type of research carried out is Classroom Action Research (PTK), with data collection techniques through observation sheets of student activities and learning outcome tests. Data analysis techniques use descriptive techniques. The subjects in this study were grade VII A students of SMP Negeri 7 Binamu, Jeneponto Regency. The results of this study show that the increase in student learning activity can be seen from the increase in learning activity of 11 students or 50%. In cycle I, there are 16 students or 72.73%, and in cycle II, there are 20 students or 90.91%; this result is by the specified indicators, namely the active and active categories, which reached 85%. The above reality is also supported by an increase in the average learning outcomes from 61.36 to 73.18 and 85.00 in the second cycle, with the level of learning completeness that also increased in each cycle, namely 5 students or 22.73%, in the first cycle there were 12 students or 54.55%, and in the second cycle there were 19 students or 86.36%. It can be concluded that the indicators of learning success criteria have been achieved in the second cycle, so the implementation of learning improvements is declared complete and complete in the second cycle.